2010
DOI: 10.1128/iai.01350-09
|View full text |Cite
|
Sign up to set email alerts
|

Trimer Stability of YadA Is Critical for Virulence of Yersinia enterocolitica

Abstract: Yersinia adhesin A (YadA) is a trimeric autotransporter adhesin with multiple functions in host-pathogen interactions. The aim of this study was to dissect the virulence functions promoted by YadA in vitro and in vivo. To accomplish this, we generated Yersinia enterocolitica O:8 mutants expressing point mutations in YadA G389, a highly conserved residue in the membrane anchor of YadA, and analyzed their impact on YadA expression and virulence functions. We found that point mutations of YadA G389 led to impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Our results are in line with previous studies that detected high CXCL1 levels in the sera of mice systemically infected with Y. enterocolitica WT, which correlated with the bacterial burden (43). The process of neutrophil recruitment within individual organs is dictated by inciting infection and the response of organ-specific tissue-resident cells (44).…”
Section: Discussionsupporting
confidence: 82%
“…Our results are in line with previous studies that detected high CXCL1 levels in the sera of mice systemically infected with Y. enterocolitica WT, which correlated with the bacterial burden (43). The process of neutrophil recruitment within individual organs is dictated by inciting infection and the response of organ-specific tissue-resident cells (44).…”
Section: Discussionsupporting
confidence: 82%
“…Assays were performed as described elsewhere (47,55) except that LB broth (at pH 8.5) supplemented with Ca 2ϩ and glycerol was used when the aggregation ability of Ec-TaaP, HI4320, or its taaP mutant was tested under alkaline conditions. Briefly, cultures were incubated to late logarithmic phase (postinduction), harvested, washed, and resuspended in phosphate buffer (at the corresponding pH) with an initial OD 600 of ϳ3.0, which was considered 100% for 0 h after the end of log-phase growth (t 0 ).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that factor H, which binds directly to YadA, acts as a cofactor for factor I-mediated degradation of C3b. However, these data also revealed that only a very small amount of C3b present in the experiments was degraded into iC3b (5,20,21). The amount of C3b typically used in these experiments was considerably lower than that of C3 in human serum.…”
Section: Discussionmentioning
confidence: 69%
“…The exchange of a highly conserved glycine within the C-terminal b-barrel membrane anchor domain by amino acids with larger side chain size (such as threonine, asparagine, histidine) reduces YadA trimer stability and eventually impaired passenger domain translocation. YadA mutants that carried the small amino acids Alanine or Serine instead of Glycine at position 389 resembled wild type expression levels and phenotype except that they were sensitive to complementdependent killing and displayed reduced trimer stability in Western blot (5,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation